A ZnS nanocrystal/reduced graphene oxide composite anode with enhanced electrochemical performances for lithium-ion batteries. Issue 44 (28th October 2016) - Feng, Yan; Zhang, Yuliang; Wei, Yuzhen; Song, Xiangyun; Fu, Yanbo; Battaglia, Vincent S.
Abstract : A simple route for the preparation of ZnS nanocrystal/reduced graphene oxide (ZnS/RGO) by a hydrothermal synthesis process was achieved. Abstract : A simple route for the preparation of ZnS nanocrystal/reduced graphene oxide (ZnS/RGO) by a hydrothermal synthesis process was achieved. The chemical composition, morphology, and structural characterization reveal that the ZnS/RGO composite is composed of sphalerite-phased ZnS nanocrystals uniformly dispersed on functional RGO sheets with a high specific surface area. The ZnS/RGO composite was utilized as an anode in the construction of a high-performance lithium-ion battery. The ZnS/RGO composite with appropriate RGO content exhibits a high reversible specific capacity (780 mA h g −1 ), excellent cycle stability over 100 cycles (71.3% retention), and good rate performance at 2C (51.2% of its capacity when measured at a 0.1C rate). To further investigate this ZnS/RGO anode for practical use in full Li-ion cells, we tested the electrochemical performance of the ZnS/RGO anode at different cut-off voltages for the first time. The presence of RGO plays an important role in providing high conductivity as well as a substrate with a high surface area. This helps alleviate the typically problems associated with volume expansion and shrinkage during prolonged cycling. Additionally, the RGO provides multiple nucleation points that result in a uniformly dispersed film of nanosized ZnS that covers its surface. Thus, the high surface area RGO enables high electronic conductivity and fast charge transfer kinetics for ZnS lithiation/delithiation.